Narrative and genre - Chamberlain, Mary, 1947-; Thompson, Paul, 1935- (Routledge studies in memory and narrative, 1998)
Narrative and Genre presents exciting new debates in an emerging field, where international academics from a plethora of disciplines examine the conventions and restrictions of language and genre and how they influence our communication.